Cross-generational effects of male reproductive success and offspring immunocompetence in Drosophila melanogaster - Ashley Guncay; Thiropa Balasubramaniam; Katie Plagens; Joel Weadge; Tristan A.F. Long (Canadian Science Publishing, 2017)
In some species where males make no direct contribution to a female's lifetime reproductive success, females choose mates based on the indirect benefits manifested in their offspring. One trait that may be subject to this sexual selection is immunocompetence (the ability to mount an immune response following exposure to pathogens); however, the results of previous work on its link to male attractiveness have been ambiguous. Herein we examine the life history consequences of mating with males with a history of failure or success in reproductive competitions in Drosophila melanogaster. By examining egg-to-adult survival, body weights, and bacterial loads of offspring reared in either the absence or presence of a bacterial pathogen, we were able to examine whether sire reproductive success was associated with their offsprings' ability to respond to an immunological challenge and other life history traits. Our results are partially consistent with the predictions of the "immunocompetence handicap hypothesis": competitively successful males ("studs") sire male offspring that are better able to handle an immunological challenge than those sired by competitively unsuccessful males ("duds"). However, our assay also revealed the opposite pattern in female offspring, suggestive of the complicating presence of alleles with sexually antagonistic effects on the expression of this important life history trait.